Automated BIM data validation integrating open-standard schema with visual programming language. (April 2019) - Ghannad, Pedram; Lee, Yong-Cheol; Dimyadi, Johannes; Solihin, Wawan
Abstract: A building design must comply with a wide spectrum of requirements stipulated by building codes, normative standards, owner's specifications, industry's guidelines, and project requirements. The current rule-based compliance checking practice is a costly bottleneck in a building project, and thus, there is a demand for a design evaluation process that incorporates automated checking capabilities to address the inefficiency and the error-prone nature of the current manual checking practice. The inherent complexity of building design rules and impracticability of existing automated checking approaches are two key challenges that must be addressed to enable practical compliance checking automation. This research study proposes a new modularized framework that integrates the emerging open standard, LegalRuleML, with a Visual Programming Language. The framework allows a standardized method of defining design rules in a machine-readable and executable format. The proposed approach encompasses the entire compliance checking process from the interpretation of natural language-based requirements to machine-readable rules, rule categorization, rule parameterization, and the execution of the rules on the ISO-standard building information model. This modularized BIM-based design validation framework is expected to help automatically and iteratively evaluate the level of quality and defects of information conveyed in a given building model as an essential part of the early design process.